EKSITENSI PENGADILAN AGAMA WATANSOPPENG TERHADAP PENANGGULANGAN PERKAWINAN ANAK MENURUT UU NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN PERSPEKTIF HUKUM ISLAM - Asriana, Ria Asriana; Lomba Sultan; Muhammad Fajri (Universitas Islam Negeri Alauddin Makassar, 2024)
The rise of child marriage often occurs in Indonesia especially in the watansoppeng religius court, increasing every year. Child marriage is a carried out by a couple whose age is less than the minimum age for marriage as determined. A child marriage as determined. A child marriage usually occurs dute to various factors including promiscuity, lack of parental guidance, so that their children will find a way so they can be happy, namely associating with people whose behavior is not seen (free). Outher factors are due to economic factors are due to economic factors, self-will factors, customs factors. This type of research includes field research located at the watansopppeng religious court using a syar’i approach. The findings of this study show that the exsistence of law No, 16 of 2019 is carried out and confirmed in accordance with the provisions of the law and is also guided by supreme court regulation No. 5 of 2019, in addition to age issues, judges must also consider child protection and the best interests of children. In 2021 where covid-19 still hit the demand for child marriage in soppeng, there was a drastic increase of 466 requests compared to 2022 of 330 requests.